PENERAPAN PEMBERIAN AROMATERAPI LAVENDERPADA KLIEN POST OPERASI APENDIKTOMI DENGAN MASALAH KEPERAWATAN NYERI AKUT DI RSUD LABUANG BAJI MAKASSAR - Nurfadilah; Rahmawati Ramli; Nur Ilah Padhila; Fatma Jama (Jurnal Kesehatan, 2026)
Appendicitis is an inflammation of the appendix that requires surgical intervention (appendectomy) and often causes acute postoperative pain. Uncontrolled pain can hinder mobilization and delay recovery. One of the effective non-pharmacological therapies to reduce pain is lavender aromatherapy, which contains linalool and linalyl acetate compounds that have calming, relaxing, and analgesic effects. To determine the effectiveness of lavender aromatherapy in reducing acute pain among post-appendectomy clients at Labuang Baji Hospital Makassar.This study used a case study method with a nursing process approach. The intervention was carried out by administering lavender aromatherapy through inhalation for 10–15 minutes, twice daily. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention to assess changes in pain level. The results showed a decrease in pain score from 6 (moderate) to 3 (mild) after lavender aromatherapy administration. The patient appeared more relaxed, comfortable, and able to rest well. This proves that lavender aromatherapy is effective as a complementary non-pharmacological therapy in reducing acute pain among post-appendectomy patients and supports the improvement of nursing care quality and recovery process.